Empowering Economic Growth in Balongdowo Village, Sidoarjo, East Java: Pioneering a Digital Tourism and Marketing Initiative - Triwiyanto, Triwiyanto; Luthfiyah, Sari; Utomo, Bedjo; Forra Wakidi, Levana (Frontiers in Community Service and Empowerment, 2024)
Balongdowo Village, recognized as the largest producer of Kupang in Sidoarjo Regency, has significant potential for economic development through its local seafood products. This community service program aims to enhance the economic sustainability of the village by empowering local businesses and introducing digital marketing strategies. The program focuses on promoting Kupang-based products through e-commerce platforms such as Tokopedia, Shopee, and Bukalapak, expanding market reach beyond the local area. Additionally, the initiative supports the development of a village information system portal to highlight the village’s profile, potential, and services. By integrating digital tools into marketing and village management, the project seeks to transform Balongdowo into a self-sufficient digital village. The program includes training sessions for local business owners and village officials on e-commerce usage, product presentation, and website management. The result is the successful establishment of online shops for local businesses and the launch of the Balongdowo village website, creating new opportunities for economic growth and improved public services.